Augmenting Cerebral Perfusion Via Bypass Technique in symptomatic intracranial atherosclerotic disease - Rajbhandari, Pravesh (Nepal Journal of Neuroscience, 2023)
In Nepal, acute ischemic stroke (AIS) holds the sobering distinction of being the fifth leading cause of mortality and the third most prevalent source of disability. This underscores a pressing health concern that demands attention and proactive measures to address its impact on public well-being. Nepal is amidst a swift epidemiological shift, witnessing a surge in stroke and noncommunicable diseases due to rapid urbanization, sedentary lifestyles, and poor dietary habits. Urgent measures are essential to address this burgeoning public health challenge.